Short-Term Study Abroad: The Storied Experiences of Teacher Candidates From Japan (LEARNing Landscapes, 2018)
The story extracts presented here reflect the experiences of five teacher candidates from Japan on a short-term study abroad program focusing on developing English-language skills while exploring Canadian culture and English-language teaching methods. Narrative inquiry techniques were employed to gather data related to the participants’ program experiences. These data were crafted into stories with participant input and review. The story extracts relate to intercultural interactions, First Nations culture, teaching methods, meals, and extracurricular activities. On reflection, the narrative inquiry process employed in this study worked as both a research and pedagogical tool to uncover meaningful program experiences.
Keywords: narrative inquiry; study abroad programs for teachers; stories and teachers